Pendampingan Usaha Produk Rice Bowl Ayam Suwir Mahasiswa Universitas Kristen Indonesia Toraja - Srisetyawanie Bandaso; Beatrix Putri Danduru; Afian Dezi Sanda Sipi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The implementation of this service activity is carried out by providing material regarding Proposal Preparation and Food Business Planning for Shredded Chicken Rice Bowl Products by delivering this training material with lectures and discussions. Mentoring is provided to provide direction on how to start business planning and preparing business proposals to marketing and business development. The aim of this assistance is to provide students with the understanding and ability to start a business well